2016
DOI: 10.1093/her/cyw014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a web-based decision aid regarding diagnostic self-testing. A single-blind randomized controlled trial

Abstract: Dutch Trial Register: NTR 3149.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Patients scored one point for each correct answer. One point was deducted for each incorrect answer; no points were given if the patient did not know the answer (appendix E) [34] .…”
Section: Methodsmentioning
confidence: 99%
“…Patients scored one point for each correct answer. One point was deducted for each incorrect answer; no points were given if the patient did not know the answer (appendix E) [34] .…”
Section: Methodsmentioning
confidence: 99%
“…Interactive visualizations can be particularly useful for location-allocation analyses given that these analyses can result in many charts and maps depending on the number of evaluated scenarios and optimisation criteria [ 23 , 24 ]. Importantly, previous research has demonstrated that interactive information can have greater impact than passive information [ 25 , 26 ]. Furthermore, the application can also serve as an interactive simulator that allows users to create and explore their own scenarios regarding health facility allocation and how this influences accessibility and health outcomes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interactive visualizations can be particularly useful for location-allocation analyses given that these analyses can result in many charts and maps depending on the number of evaluated scenarios and optimization criteria (e.g., [22,23]). Importantly, previous research has demonstrated that interactive information can have greater impact than passive information (e.g., [24,25]). Furthermore, the application can also serve as an interactive simulator that allows users to create and explore their own scenarios regarding health facility allocation and how this influences accessibility and health outcomes [26].…”
Section: Introductionmentioning
confidence: 99%